The Future of Subject in Post-Coronavirus World in the Light of Foucault’s Technology of the Self - Aulia Rakhmat (Studia Philosophica et Theologica, 2022)
This paper aims to present the relevance of Foucault’s technology of the self to face the future of the post-coronavirus world. The significance of Foucault technology of the self lies in the practice of self-forming where the pandemic era has urged humans to evaluate their subjectivity. It is because the subject is faced with the external challenge of the biopolitics of the state as well as internal challenge of the Subject’s future anxiety. Hence, this study tries to respond to these problems by analyzing Foucault's technology of the self which was inspired by the ancient practice of the care of the self to practice self-examination in order to achieve self-mastery. In compiling this paper, the author applied a qualitative methodology through which descriptive, textual, and contextual analyses are applied to written materials related to the subject matter. By developing self-mastery techniques, Foucault presupposes the individual to be a critical and reflective subject who will actively respond to biopolitics as well as his own subjectivity.